LIQUID CRYSTAL DISPLAY DEVICE - SEIKI MASAHIRO; HASHIMOTO MIYUKI; YAMADA YUMIKO (1998)
PROBLEM TO BE SOLVED: To provide a liquid crystal device permitting to have a stable auxiliary capacity value, obtain a uniform gap between substrates by arranging cylindrical spacers and achieve a good display. SOLUTION: In an auxiliary capacity part of a TFT array substrate in this liquid crystal display device, an electrode 24 for an auxiliary capacity formed in a same layer as data wiring 9 is arranged via a gate insulation film 17 on address wiring 8, and an auxiliary capacity 16 is formed from this electrode 24 for the auxiliary capacity and the lower layer of the address wiring 8. Further, in a contact hole 25 provided in such an auxiliary capacity part 16, a cylindrical spacer 26 formed from laminated layers of colored layers on the opposing substrate side is accommodated for an arrangement and keeps a fixed gap between the substrates.